THE CONCEPTS “HOME” AND “FAMILY” IN ENGLISH PROVERBS AND SAYINGS (Konferensiyalar | Conferences, 2024)
It is no coincidence that the concepts “home” and “family” are united, because home is in the traditional consciousness of all peoples, it is not only a structure or a roof over one’s head, but also a dwelling for the body and spirit.